Doublecortin-Expressing Neurons in Chinese Tree Shrew Forebrain Exhibit Mixed Rodent and Primate-Like Topographic Characteristics - Ai, Jia-Qi; Luo, Rongcan; Tu, Tian; Yang, Chen; Jiang, Juan; Zhang, Bo; Bi, Rui; Tu, Ewen; Yao, Yong-Gang; Yan, Xiao-Xin (Frontiers in Neuroanatomy, 2021)
Doublecortin (DCX) is transiently expressed in new-born neurons in the subventricular zone (SVZ) and subgranular zone (SGZ) related to adult neurogenesis in the olfactory bulb (OB) and hippocampal formation. DCX immunoreactive (DCX+) immature neurons also occur in the cerebral cortex primarily over layer II and the amygdala around the paralaminar nucleus (PLN) in various mammals, with interspecies differences pointing to phylogenic variation. The tree shrews (Tupaia belangeri) are phylogenetically closer to primates than to rodents. Little is known about DCX+ neurons in the brain of this species. In the present study, we characterized DCX immunoreactivity (IR) in the forebrain of Chinese tree shrews aged from 2 months- to 6 years-old (n = 18). DCX+ cells were present in the OB, SVZ, SGZ, the piriform cortex over layer II, and the amygdala around the PLN. The numerical densities of DCX+ neurons were reduced in all above neuroanatomical regions with age, particularly dramatic in the DG in the 5–6 years-old animals. Thus, DCX+ neurons are present in the two established neurogenic sites (SVZ and SGZ) in the Chinese tree shrew as seen in other mammals. DCX+ cortical neurons in this animal exhibit a topographic pattern comparable to that in mice and rats, while these immature neurons are also present in the amygdala, concentrating around the PLN as seen in primates and some nonprimate mammals.